Prediction of transposable elements (2019)
Transposable Elements (TEs) play a fundamental role on the DNA sequences in eukariotic genomes. Their nature imply they form repetitive regions, which control the structure, rearrangement and regulatory functions inside our genome. With the new sequencing techniques and the lack of bioinformatic software that is capable of predicting TEs, arise the problem of detecting these sequences. Using an approach based on kmer search on an FM-Index we were able to indentify type I retrotransposons. Finally, we measured the effectivity of our proposed method in the Saccharomyces genome database obtaining 68.19% of precision, 58.82% of recall and 63.15% of F-measure. A further evaluation is needed using other genomes that vary their composition of repetitive elements to determine the performance of the proposed method.